Climate Change Implication on Palestine: A Case Study Jenin Governorate (American Journal of Multidisciplinary Research and Innovation, 2023)
Climate change negatively affects sustainable development in Palestine, especially Jenin Gover-norate, which is the food basket for Palestine. This study identified climate change variables in Jenin Governorate for more than 100 years, especially temperatures and precipitation, derived from historical data to study the manifestations of climate change and its impact on water re-sources and the agricultural sector. The impact of climate change on groundwater wells is an un-derstatement. The majority of Jenin’s water wells, which number about 66 (including 22 agricul-tural wells), are located in the northeastern basin. By analyzing the data for the average annual total recharge of this basin, it was evident that the recharge had decreased from about 151 million cubic meters/year from 1976-1992 to about 134 million cubic meters/year during 1993-2009. (about 11.3%). This is because of the general solid decrease in rainfall in the Jenin area due to the effects of climate change. The decrease in recharge, coupled with increased groundwater pump-ing, has drained the reservoir stock and deteriorated the groundwater quality. The other source of water in Jenin Governorate is springs. Jenin Governorate has 42 streams largely used for small-scale agricultural and household needs. The research showed that the discharge of the springs increases from 2014 to 2020 (average discharge 0.48 MCM/yr.) compared to the period 2001 to 2011 (average discharge 0.48 MCM/yr.). years) due to the increase in the amounts of discharge from the springs and the start of relying on them more, as Jenin governorate is facing water scarcity recently. In the future, climate change will considerably impact water resources, altering surface and underground water supplies for residential and commercial purposes, irriga-tion, in-stream ecosystems, and aquatic leisure.